Dynamics of HIV-1 RNA Near the Plasma Membrane during Virus Assembly - Sardo, Luca (J Virol, 2015)
To increase our understanding of the events that lead to HIV-1 genome packaging, we examined the dynamics of viral RNA and Gag-RNA interactions near the plasma membrane by using total internal reflection fluorescence microscopy. We labeled HIV-1 RNA with a photoconvertible Eos protein via an RNA-binding protein that recognizes stem-loop sequences engineered into the viral genome. Near-UV light exposure causes an irreversible structural change in Eos and alters its emitted fluorescence from green to red. We studied the dynamics of HIV-1 RNA by photoconverting Eos near the plasma membrane, and we monitored the population of photoconverted red-Eos-labeled RNA signals over time. We found that in the absence of Gag, most of the HIV-1 RNAs stayed near the plasma membrane transiently, for a few minutes. The presence of Gag significantly increased the time that RNAs stayed near the plasma membrane: most of the RNAs were still detected after 30 min. We then quantified the proportion of HIV-1 RNAs near the plasma membrane that were packaged into assembling viral complexes. By tagging Gag with blue fluorescent protein, we observed that only a portion, ∼13 to 34%, of the HIV-1 RNAs that reached the membrane were recruited into assembling particles in an hour, and the frequency of HIV-1 RNA packaging varied with the Gag expression level. Our studies reveal the HIV-1 RNA dynamics on the plasma membrane and the efficiency of RNA recruitment and provide insights into the events leading to the generation of infectious HIV-1 virions. IMPORTANCE Nascent HIV-1 particles assemble on plasma membranes. During the assembly process, HIV-1 RNA genomes must be encapsidated into viral complexes to generate infectious particles. To gain insights into the RNA packaging and virus assembly mechanisms, we labeled and monitored the HIV-1 RNA signals near the plasma membrane. Our results showed that most of the HIV-1 RNAs stayed near the plasma membrane for only a few minutes in the absence of Gag, whereas most HIV-1 RNAs stayed at the plasma membrane for 15 to 60 min in the presence of Gag. Our results also demonstrated that only a small proportion of the HIV-1 RNAs, approximately 1/10 to 1/3 of the RNAs that reached the plasma membrane, was incorporated into viral protein complexes. These studies determined the dynamics of HIV-1 RNA on the plasma membrane and obtained temporal information on RNA-Gag interactions that lead to RNA encapsidation.